A student's handbook of Indian aesthetics - Gupta, Neerja A. (Cambridge Scholars Publishing, 2017)
Art and life in India have been inextricably intertwined from ancient times to the present day. Art as a way of life, as ritual, as decoration and as unity with the Sublime bore testament to the socio-cultural milieu; the high level of sophistication that developed in ancient India was reflected in the arts in a holistic light. The arts, thus, strived to hone man's intellectual sensibilities, thus raising him to the level of the transcendental, which in India was Brahma or ultimate reality. This book brings forth the popular theories of Indian aesthetics and Indian poetics. Bharatmuni, Abhinavg.